Negotiating boundaries and borders qualitative methodology and development research - Smith, Matt, Dr. (Oxford ; Amsterdam ; San Diego, CA ; Elsevier, 2007)
As international development presents enormous moral, political and ethical challenges, so researching and understanding it requires negotiation of its contested contours. The chapters draw on research conducted around the world using a range of methodologies, perspectives and commitments, rooted in diverse disciplines. Through their exploration of the interrelationship of qualitative methodologies and development theory, policy and practice, the book demonstrates the importance of placing qualitative methodologies within their conceptual, practical and political contexts. It also highlights the important but contested contribution that qualitative methodology can make to not only understanding development, but engendering it. This book explores qualitative methodology and development in terms of the ways researchers negotiate boundaries and borders. It asks questions of development research, critiques relationships between researchers and subjects, and challenges connections between research and change. It demonstrates the importance of placing qualitative methods within their right context. This book series is available electronically online.
What counts as development research? / Darryl Humble, Matt Smith -- Researching transnational advocacy networks: methods and challenges for development / Helen Yanacopulos -- Researching with, not on: using photography in researching street children in Accra, Ghana / Phil Mizen, Yaw Ofosu-Kusi -- Feminist methodologies: unsettling multiple boundaries in development / Katy Jenkins -- Development ethics and moral engagement: some political and ethical dilemmas in development research / John Donnelly -- When things are not as they seem: untangling the webs of a South-Indian NGO / James Staples -- Hearing voices? : negotiating multiple ethical commitments in development research / Kate Simpson -- Researching for change / Mary Mellor -- Acceptable stories or acceptable boundaries? : on managerial optimism, critical reflection, and one particularly intractable development organisation / Ingie Hovland -- Breaching the borders between research and practice: development NGOs and qualitative data / Oliver Bakewell.
Title from e-book title screen (viewed Oct. 8, 2007).
Includes bibliographical references and index.
Description based on print version record.
Keywords: Qualitative research -- Methodology; Boundaries; Economic development -- Research; Political development -- Research; Social planning -- Research; Social research & statistics; Social Science -- Sociology -- General; Social Science -- Statistics; Developing countries -- Research